2011 18th IEEE Workshop on Local &Amp; Metropolitan Area Networks (LANMAN) 2011
DOI: 10.1109/lanman.2011.6076940
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing fairness for 3G wireless networks

Abstract: The end to end system data performance over a 3G cellular network depends on many factors such as the number of users, interference, multipath propagation, radio resource management techniques as well as the interaction between these mechanisms and the transport protocol's flow and congestion mechanisms. Using controlled experiments in a public cell site, we investigate the interaction between TCP and the 3G UMTS/HSPA network's resource allocation, and its effect on fairness in the throughput achieved across m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…RNCs manage control signaling such as Radio Access Bearer (RAB) assignments, transmission scheduling, and handovers. Each UE negotiates allocation of radio resources with the RAN based on a wide range of factors, such as available radio resources and signal strength [6].…”
Section: Cellular Network Backgroundmentioning
confidence: 99%
“…RNCs manage control signaling such as Radio Access Bearer (RAB) assignments, transmission scheduling, and handovers. Each UE negotiates allocation of radio resources with the RAN based on a wide range of factors, such as available radio resources and signal strength [6].…”
Section: Cellular Network Backgroundmentioning
confidence: 99%
“…It has been widely assumed that TCP can provide fair performance for multiple flows. However, measurement studies over a 3G network [9] has shown that the fairness among multiple competing TCP flows fluctuates significantly when the lasthop cellular link is the bottleneck, i.e., TCP can achieve rather unfair throughput (more than 5 times difference) in cellular networks. The major cause behind this phenomenon is the poor interaction between TCP congestion control and proportional fair (PF) scheduling in cellular networks.…”
Section: A Issues Of Has Over Cellularmentioning
confidence: 99%
“…Thus the instable and unfair playback will be inevitably introduced. More unfortunately, measurement studies [9] have shown that the prevalent assumption of TCP fairness may not be true in cellular networks. This indicates that multiple clients would not achieve fair performance even though they somehow learn the channel information and request the true bandwidth share.…”
Section: Introductionmentioning
confidence: 99%
“…We also consider network related metrics such as resource utilisation and fairness, which is estimated as [17] …”
Section: A Dash Encoding Setupmentioning
confidence: 99%